Targeted treatments for multiple myeloma: specific role of carfilzomib - Sugumar D; Keller J; Vij R (Dove Medical Press, 2015)
Dhivya Sugumar,1 Jesse Keller,2 Ravi Vij2 1Department of Internal Medicine, St Mary’s Health Center, 2Department of Medicine, Division of Oncology, Washington University in St Louis, St Louis, USA Abstract: Carfilzomib is a selective, irreversible proteasome inhibitor, initially approved in the US in 2012 as single-agent therapy for relapsed and refractory multiple myeloma. Numerous Phase II studies have evaluated carfilzomib in the relapsed and refractory as well as the newly diagnosed setting, and Phase III studies are entering their final analysis. Data continue to grow to support its use as both single-agent therapy and in combination with immunomodulatory and other novel agents. This review discusses the role of carfilzomib in the treatment of multiple myeloma. Its mechanism of action, pharmacokinetics, and role in clinical management will be reviewed. Keywords: relapsed and refractory, targeted therapy, proteasome inhibitor, novel agents